Danielle Armstrong: capstone - Armstrong, Danielle, artist (Colorado State University. Libraries, 2026)
The artist's statement: Why Revisit my childhood at this point in my life? Graduating college marks a shift into adulthood, bringing new responsibility, change, and awareness. With that, I return to my childhood; not to escape the present, but to remember and understand where my sense of comfort, love, and identity began. We Played Until It Got Dark explores memory as something that shifts overtime. It is not a documentation of events as they happened, but as they are remembered now. They are filtered through growth, distance, and reflection. Looking through old photos brought a sense of happiness and longing, but also an awareness of how differently those moments exist in my memory. The piece takes the form of an accordion-style book, allowing all pages to exist together as one continuous work while also functioning as individual moments. This structure mirrors the way my memories have unfolded: nonlinear, connected, and with many layers of emotion. Each spread is inspired from specific memories, such as summers spent with my older sister riding bikes and drawing with chalk outside, capturing that nostalgia and calmness tied to that time. Another, remembering times of me and my sister dressing up in princess costumes, incorporating the actual wand and costume elements which act as a physical extension of the memory itself. Material choices play the central role. Textured paper, fabric scraps, lace, and gold leaf, each representing something different for me: comfort, delicacy, value. Some materials come directly from my childhood, reinforcing that connection between object and memory. Similar to the idea that "smell holds memory", these materials act as anchors for me bringing the past into the present. Visually, the work leans into warm, muted tones to echo the faded quality of old photographs and distant memories. Images printed on thin, almost transparent paper allow layering to create depth. Negative space is also used intentionally to give each moment room to exist. Viewers should feel they can move at their own pace through each page and feel their own emotions that resonate with the work. Rather than presenting childhood as fixed or purely nostalgic, We Played Until It Got Dark considers how memory evolves and how those early experiences continue to shape identity in adulthood. There is growth, expanded knowledge, and that sense of peace a child has, but doesn't realize it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making